Analisis Dampak Meningkatnya Harga Kebutuhan Bahan Pokok di Pasar Limau Purut - Fadhila, Irwan; Movitaria, Mega Adyna (Institut Agama Islam Sumatera Barat Pariaman, 2022)
The increasing price of basic needs is now 2 times the previous price, where the previous price was Rp. 40,000/kg to Rp. 100,000/kg. The purpose of this study was to determine the impact of rising prices for basic commodities on the community. This study uses a qualitative descriptive method. The results of the study found that the reduced welfare of the community was caused by the rising prices of basic commodities. As well as the inability of the people's purchasing power to meet basic needs, especially in the Limau Purut market